2021
DOI: 10.1155/2021/7287796
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Tuning of PID Controller for Beer Filling Machine Liquid Level Control Based on Improved Genetic Algorithm

Abstract: Parameter tuning of PID controller for liquid level control of beer filling machine was studied in this paper, which can meet the demand of accurate controlling in beer production and improve the rapidity under the same conditions. Firstly, an improved genetic algorithm was proposed which has been verified by eight kinds of test functions. Simulation results revealed that, in comparation with other modified particle swarm optimization algorithm and modified genetic algorithm, the algorithm proposed in this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…ese rules are then used to control the system. us, fuzzy control is particularly suitable for simulation experts' control of unknown, complex, and nonlinear systems of mathematical models [13,14]. e fuzzy control system is similar to the common negative feedback closed-loop control system.…”
Section: Fuzzy Control Conceptmentioning
confidence: 99%
“…ese rules are then used to control the system. us, fuzzy control is particularly suitable for simulation experts' control of unknown, complex, and nonlinear systems of mathematical models [13,14]. e fuzzy control system is similar to the common negative feedback closed-loop control system.…”
Section: Fuzzy Control Conceptmentioning
confidence: 99%
“…To address this issue, researchers have been actively exploring the potential of metaheuristic algorithms, which offer robust and adaptive optimization capabilities in tackling complex control problems [11]- [14]. Among these algorithms, a promising contender is the particle swarm optimization [15], modified grey wolf optimization [16], cuckoo search algorithm [17], [18], and improved genetic algorithm [19], along with non-dominated sorting genetic algorithm and multiobjective particle swarm optimization [20]. The primary objective in the context of this study is to design and implement a PID controlled three-tank liquid level system using the prairie dog optimization (PDO) [21] as a novel metaheuristic algorithm in this specific field of research.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], the hydraulic servo system uses a genetic algorithm to search for the optimal PID controller gain to achieve accurate control of the displacement of the valve-controlled hydraulic cylinder in the system. Xiao et al [6] proposed an improved genetic algorithm and verified it using eight test functions. The results showed that the probability of convergence to the optimal value was improved, and it was verified on a beer-filling machine system.…”
Section: Introductionmentioning
confidence: 99%